BOS FUND MANAGEMENT STRATEGY IN FACING THE INDUSTRIAL REVOLUTION 4.0 - Irfan Maulana Sidik; Rais Hidayat; Widanengsih Fujiastuti (Adisam Publisher, 2024)
Improving the quality of education is an important priority in national development, therefore encouragement from the central and local governments is needed to take concrete actions in realizing a better and quality education system. The government provides tuition assistance for schools, namely in the form of School Operational Assistance Funds (BOS) With 4 strategies, school organization institutions can maximize the process of using BOS funds so that it is more effective with effective strategies in managing BOS funds in schools: 1) Efficient and careful planning, 2) Allocation of budgets in accordance with the rules 3) the use of BOS funds, 4) Good bookkeeping of BOS funds so that they can be accounted for. Along with developments in the industrial revolution era, school institutions can improve to develop effective strategies in facing the industrial revolution era by: The use of technology (ICT) in the process of making BOS reports through the ARKAS, SIMDA and SIPDA applications, digital education, for example by maximizing the use of BOS funds for the benefit of digital development potential in the process of improving the quality of learning in order to compete and survive in the era industry 4.0, digital skills development The use of BOS can be maximized through digital literacy activities, seminars and workshops, collaborating with the industry to gain support in the learning process, and conducting innovative funding such as: development of digital labs, digital libraries, and digital-based schools